Normal-temperature curing environment-friendly silicon-based nano coating as well as preparation method and application thereof
The silicon-based coating formulation addresses the challenge of balancing thermal insulation, electrical resistance, and surface wetting by using a specific composition and adjustable properties, improving performance in demanding applications.
Patent Information
- Application Number
- CN202510591136.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-08
- Publication Date
- 2025-07-15
- Estimated Expiration
- 2045-05-08
AI Technical Summary
The prior art is difficult to take into account both heat resistance, insulation and wetting properties under complex working conditions, which limits the application range and improvement of technical indicators of silicon-based coatings.
Silicon-based nanocoating components based on weight parts, including silicone oil base composition, hydrophilic and regulatory matrix, matrix reinforcement fiber, aniline formaldehyde resin and diluent, were prepared by a normal temperature curing method to regulate surface wetting.
It achieves high insulation, heat resistance and improved wetting properties cured at room temperature, is suitable for high temperature and high pressure environments, and the wetting properties of the coating surface can be adjusted.
Smart Images

Figure CN120310429A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of chemical synthesis, and more specifically, to a room-temperature curable environmentally friendly silicon-based coating, a preparation method thereof, and an application thereof. Background Art
[0002] Organosilicon-inorganic silicon series coatings can develop materials and coatings with good heat insulation and insulation properties due to their organic-inorganic hybrid structure. Moreover, in the fields of ordinary civil and industrial applications, surfaces with specific wettability are often required, such as pipeline flow control and detection, high-temperature and high-pressure monitoring, intelligent building facades, automotive exterior surfaces, etc. Under complex working conditions, composite application scenarios of heat, electricity, and surface wettability states are often required for organosilicon-inorganic composite coatings. Although there are some heat-resistant thermal insulation layer technologies in the related art, it is generally difficult to balance or have a well-controlled wettable surface, which limits the application range and improvement of technical indicators of the silicon-based coating.
[0003] For example, Chinese Patent Publication No. CN119569418A discloses a manufacturing method of a low thermal conductivity and high-temperature resistant silicon dioxide aerogel thermal insulation layer. However, this technology does not disclose or achieve good dielectric breakdown resistance and insulation characteristics, nor does it consider the regulation of the wettability characteristics of the surface of the object to which it is applied.
[0004] Therefore, there is still a need in this field for a room-temperature curable, highly insulating and heat-resistant coating and a corresponding coating. Through appropriate molecular structure design and filler component regulation, a more regular coating stacking structure can be achieved, in order to balance the application requirements of heat resistance, insulation, and wettable surfaces. Summary of the Invention
[0005] The purpose of the present invention is to solve one or more deficiencies in the above-mentioned existing technologies, provide a silicon-based coating, and provide a room-temperature curable environmentally friendly silicon-based nano-coating, a preparation method thereof, and an application thereof, in order to improve the application requirements of heat resistance, insulation, and wettable surfaces, and at the same time facilitate the operation of users and the control of surface wettability during regulation.
[0006] In the first aspect of the present invention, there is provided a room-temperature curable silicon-based nano-coating, wherein, by weight, the silicon-based nano-coating comprises raw materials of the following components:
[0007] Silicone oil base composition: 150 to 200 parts by weight;
[0008] Hydrophilic-hydrophobic regulation matrix: 15 to 35 parts by weight;
[0009] Matrix reinforcing fiber: 5 to 30 parts by weight;
[0010] Aniline formaldehyde resin: 10 to 30 parts by weight;
[0011] Diluent: 10 to 30 parts by weight; and
[0012] wherein the silicone oil base composition comprises an epoxy-terminated silicone oil having a weight average molecular weight of 10,000 to 12,000, a bifunctional phenyl vinyl silicone oil having a weight average molecular weight of 600 to 800, a bifunctional phenyl hydrogen-containing silicone oil having a weight average molecular weight of 600 to 900, and an adhesion enhancing component; and
[0013] wherein the hydrophilic-hydrophobic regulation matrix comprises silica particles with two or more different particle size distributions.
[0014] In a further optional embodiment, the hydrophilic-hydrophobic regulation matrix comprises silica particles with three different particle size distributions, and
[0015] wherein the first silica particle is nano-silica having an average particle size (D50) of 8 to 15 nm, and it accounts for 10 wt% to 20 wt% of the total mass of the silica particles;
[0016] the second silica particle is nano-silica having an average particle size (D50) of 50 to 75 nm, and it accounts for 30 wt% to 45 wt% of the total mass of the silica particles;
[0017] the third silica particle is silica particle having an average particle size (D50) of 1 to 3 microns, and it accounts for 40 wt% to 50 wt% of the total mass of the silica particles; and
[0018] the mass ratio of the silicone oil base composition to the hydrophilic-hydrophobic regulation matrix is between 10:(1 - 2).
[0019] In a further optional embodiment, calculated based on 100 wt% of the total weight of the silicone oil base composition, the silicone oil base composition comprises:
[0020] 25 wt% to 30 wt% of an epoxy-terminated silicone oil having a weight average molecular weight of 10,000 to 12,000;
[0021] 55 wt% to 60 wt% of a bifunctional phenyl vinyl silicone oil having a weight average molecular weight of 600 to 800;
[0022] 5 wt% to 10 wt% of a bifunctional phenyl hydrogen-containing silicone oil having a weight average molecular weight of 600 - 900;
[0023] 0.5 wt% to 1 wt% of an adhesion enhancing component;
[0024] 0.1 wt% to 1 wt% of a control agent; and
[0025] anhydrous ethanol as a solvent.
[0026] In a further optional solution, the room temperature curable silicon-based nano coating further satisfies one or more of the following conditions:
[0027] The matrix reinforcing fiber is a quartz fiber with an average length of 20 microns to 40 microns and an aspect ratio greater than 10:1;
[0028] The diluent is ethyl acetate;
[0029] The room temperature curing silicon-based nano coating contains tetrabutyl titanium as an auxiliary catalyst; and
[0030] The hydrophilicity and hydrophobicity regulating matrix is prepared by mixing and stirring the silicon oxide particles with ethyl orthosilicate and heptadecafluorodecyltrimethoxysilane.
[0031] In a further optional solution, the room temperature curable silicon-based nano coating is prepared by a method comprising the following steps:
[0032] Step 1): preparing various raw material components of the silicone oil base composition, and stirring the various components in a blender to obtain a silicone oil base composition;
[0033] Step 2): prepare 5 to 10 parts by weight of deionized water, put the measured silica particles of the hydrophilicity and hydrophobicity regulating matrix into the mixed solution and stir; then, add 5 to 10 wt% of ethyl orthosilicate and 1 to 5 wt% of heptadecafluorodecyltrimethoxysilane, which account for 5 to 10 wt% of the total solid content in the hydrophilicity and hydrophobicity regulating matrix, and stir thoroughly until the mixed system is free of stratification; obtain the hydrophilicity and hydrophobicity regulating matrix;
[0034] Step 3): mixing the hydrophilicity and hydrophobicity regulating matrix with the silicone oil base composition, adding corresponding weight portions of reinforcing fibers, and stirring to obtain a first intermediate;
[0035] Step 4): adding aniline formaldehyde resin of corresponding proportion to the first intermediate, and mixing them to obtain a second intermediate;
[0036] Step 5): Mix the second intermediate with 3-5 parts by weight of an auxiliary catalyst, add a corresponding part by weight of a diluent, stir and mix, and obtain a room temperature curable silicon-based nano coating.
[0037] The second aspect of the present invention provides a method for preparing an environmentally friendly silicon-based nano-coating that is cured at room temperature.
[0038] The room temperature curable silicon-based nano coating described in any one of the above items is applied to the surface of a device or a substrate, and cured at room temperature for 96 to 120 hours to obtain the silicon-based nano coating.
[0039] Among further optional solutions, in the preparation method of the room-temperature curable environmentally friendly silicon-based nano-coating, the thickness of the silicon-based nano-coating is between 500 microns and 5 millimeters.
[0040] According to the third aspect of the present invention, there is provided an application of a room-temperature curable environmentally friendly silicon-based nano-coating, and the coating prepared by the preparation method of the room-temperature curable environmentally friendly silicon-based nano-coating is applied to the surface of the pipeline of a microfluidic device, the outer surface of a building, or the outer surface of a new energy vehicle.
[0041] For the coating according to the present invention, preferably, after the coating is applied to the corresponding surface, the wetting angle between the coating surface and a water droplet varies between 10° and 170°.
[0042] The room-temperature curable environmentally friendly silicon-based nano-coating prepared according to the embodiments of the present invention exhibits improved thermal conductivity, breakdown field strength, and heat resistance in property tests and applications. Further, the environmentally friendly silicon-based nano-coating involved in the present invention can also regulate the wetting properties of the surface within a reasonable range according to the application scenario.
[0043] Hereinafter, in combination with specific embodiments, the technical solutions and advantages of the present invention will be explained and described in more detail. It should be understood that the content presented in the specification and specific embodiments is only for more clearly explaining the technical solutions and advantages of the present invention, and does not constitute a limitation on the protection scope of the present invention. Those skilled in the art can obtain modified technical solutions based on the disclosed content of the specification. As long as they do not depart from the spirit of the present invention, all modified technical solutions should be understood to be included within the protection scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In this specification, additional drawings are used to provide further understanding of the technical solutions of the present disclosure, and form a part of the specification. Together with the specific embodiments of the present application, they are used to explain the technical solutions of the present disclosure, and do not constitute a limitation on the technical solutions of the present disclosure.
[0045] Figure 1 is a schematic photograph of a microfluidic chip for the implementation and application of the room-temperature curable environmentally friendly silicon-based nano-coating of the present invention;
[0046] Figure 2 is a schematic diagram of a device for implementing the control and adjustment of the wettability of the room-temperature curable environmentally friendly silicon-based nano-coating of the present invention;
[0047] Figure 3 is a photograph of the water droplet wetting angle during the wettability regulation of the room-temperature curable environmentally friendly silicon-based nano-coating manufactured according to Example 1 of the present invention (hydrophilic regulation);
[0048] Figure 4 It is a photograph of the water droplet wetting angle during the regulation of the wettability of a room-temperature curing environmentally friendly silicon-based nano-coating manufactured according to Embodiment 1 of the present invention (hydrophobic regulation).
[0049] Reference numerals in the accompanying drawings of the specification:
[0050] 101 - DC power supply; 102 - electrode plate; 103 - substrate; 104 - coating; 105 - heating sheet; Detailed implementation manners
[0051] The present invention is described in more detail below to facilitate the understanding of the invention.
[0052] Before the description of the specific embodiments, those skilled in the art can select appropriate raw materials according to the disclosure and teachings of the present disclosure, and use relevant testing equipment to conduct relevant tests and obtain corresponding results. For raw materials without specifying the specific manufacturer or source, those skilled in the art can select raw materials that meet the corresponding requirements as the starting materials for the reaction according to the disclosure content and requirements of this specification. The reaction raw materials of some compounds in the process come from the preliminary products or semi-finished products synthesized in the previous steps of the present invention, which is also understandable according to the present disclosure.
[0053] Table 1 schematically describes the main raw materials used in the present invention and the corresponding acquisition channels or raw material origins. It should be noted that the raw materials not described in the present invention are raw material varieties that those skilled in the art can obtain according to common technical knowledge and existing market products.
[0054] Table 1: Sources and Usage Instructions of Some Raw Materials
[0055]
[0056] Note 1: Some experiments of the present invention also used products of the RH-NB-ES10K series of terminal epoxy block polyether silicone oil provided by Ningbo Runhe New Materials Technology Co., Ltd.;
[0057] Note 2: In the series of experiments of the inventor, products of the Silicone 100 series of BASF Corporation can also be used, etc.;
[0058] Note 3: According to the experimental effects tested by the inventor, in the adhesion enhancement component, products of the Scotch-Weld series produced by 3M Company are preferably used. TM However, the present invention is not limited to this. In the series of experiments of the inventor, products of the 770 series of Henkel Corporation and the Dow series of Dow Corning Corporation can also be used. 770 TM series, Dow series of Dow Corning Corporation 1200 Primer, of Huntsman Corporation 2021, and of BASF Corporation EP21LV series products, etc.
[0059] The particle size in the embodiments of the present invention is represented by the average particle size. In a preferred embodiment, the D50 particle size is used to represent the average particle size, but the present invention is not limited thereto, and the average particle size indicated by other parameters (for example, D90, D97, etc.) can also be used.
[0060] In this experimental example, the standards related to the heat resistance of the silicone coating can be implemented with reference to the corresponding national, industrial or international standards. Without limitation, in a more specific test, the thermal conductivity can be referred to ASTM D5470; in the withstand voltage test, it can be implemented with reference to the IEC 60243 standard issued by the International Electrotechnical Commission; and the heat resistance characteristics can be referred to the relevant test process through a wind tunnel experiment (JGJ / T338 - 2014). Among them, for example, a thermal load applied to the coating by simulating high-temperature air flow is equivalent to 370 kilowatts of thermal energy passing through per square meter of the area of the coating and the workpiece. This is a relatively high thermal load, aiming to test the performance of the coating in a harsh thermal environment. For the back text parameters, under the high-temperature thermal load, it is confirmed whether the coating can still maintain a low back surface temperature in a high heat flux density environment to meet the actual application requirements.
[0061] It should be noted that for the technical solutions, the embodiments of the specification and the invention content part of the present invention that point out percentages, generally specific explanations will be made. If no special explanation is made for the concentration or percentage, then it will refer to the mass percentage (wt%), or the weight parts of each component measured in the same unit are used to describe or calculate.
[0062] Example 1
[0063] This example describes the formulation and preparation method of a typical room temperature curable silicone-based nano-coating.
[0064] In the following formulations, if there is no other special explanation, the quantity of each raw material is described by the corresponding weight parts. First, generally speaking, the components of the silicone-based nano-coating in this example mainly include the following components:
[0065] Silicone oil base composition: 200 weight parts;
[0066] Hydrophilic-hydrophobic regulation matrix: 20 weight parts;
[0067] Matrix reinforcing fiber: 10 weight parts;
[0068] Aniline formaldehyde resin: 20 weight parts;
[0069] Diluent: 15 parts by weight.
[0070] More specifically, in a typical embodiment of the present invention, each component can be obtained by the following methods:
[0071] The silicone oil base composition includes (by mass percentage): 25 wt% of an end-epoxy silicone oil with a molecular weight (weight-average molecular weight, the same below) of 10,000 to 12,000, 60 wt% of a bifunctional phenyl vinyl siloxane with a molecular weight of 600 to 800, 10 wt% of a bifunctional phenyl hydrogen-containing silicone oil with a molecular weight of 600 - 900, 0.8 wt% of an adhesion enhancement component (Scotch-Weld TM DP-8405NS, from 3M TM Company), 0.3 wt% of a control agent (1-ethynylcyclohexanol), and the balance of absolute ethanol as an auxiliary solvent; generally, the above components can be fully stirred evenly in a high-speed mixer to obtain the silicone oil base composition;
[0072] Hydrophilic-hydrophobic regulation matrix: In this experimental example, the hydrophilic-hydrophobic regulation matrix is preferably a composition of silica (SiO2) particles with a certain mass ratio within a specific particle size range. In a typical Example 1, based on 100 wt% of the hydrophilic-hydrophobic regulation matrix, it contains 15 wt% of nano-silica with an average particle size (D50) of 8 - 15 nm, 40 wt% of nano-silica with an average particle size (D50) of 50 - 75 nm, and 45 wt% of silica particles with an average particle size (D50) of 1 to 3 micrometers (μm); the coating components of the hydrophilic-hydrophobic regulation matrix can be obtained by existing methods. And, those skilled in the art are aware that there will be corresponding cavities or pores in the silica particles. In a typical Example 1:
[0073] Take 5 parts by weight of deionized water, add the weighed above-mentioned hydrophilic-hydrophobic regulation matrix to the deionized water and stir well for 60 minutes, and control the stirring speed at 150 - 200 revolutions per minute; subsequently, add 10 wt% of tetraethyl orthosilicate and 5 wt% of 1H,1H,2H,2H-perfluorodecyltrimethoxysilane based on the total mass of the solid content of the above-mentioned hydrophilic-hydrophobic regulation matrix, and stir well until the mixed system has no layering (usually the stirring time needs to be greater than 24 hours and the stirring speed is greater than 200 revolutions per minute); obtain the hydrophilic-hydrophobic regulation matrix component;
[0074] Mix the silicone oil base composition and the prepared hydrophilic-hydrophobic regulation matrix according to the weight parts, add matrix reinforcing fibers (quartz fibers with an average fiber length of 20 - 40 micrometers and an aspect ratio greater than 10:1), and stir well to obtain the first intermediate;
[0075] To the obtained first intermediate, an aniline-formaldehyde resin in a corresponding ratio is added, and a second intermediate is obtained after mixing;
[0076] The second intermediate and a co-catalyst (tetrabutyl titanate, TBT, calculated according to each weight part of the components of the silicon-based nano-coating, the co-catalyst accounts for 3-5 weight parts. If the production cost permits, a platinum-based catalyst can also be used, and the platinum content of the catalyst can be 3000-5000 ppm) are added, and then a diluent (for example, ethyl acetate is used in the examples) is added. Then it is sprayed on the surface of the device or substrate to be applied, and cured at room temperature for 96 to 120 hours to achieve the preparation of a coating with a thickness of, for example, 500 microns - 6 mm; if required according to the application field, it can also be further cured under mild heating conditions (such as at 40°C to 60°C for 24 to 48 hours).
[0077] Examples 2 to 4
[0078] Based on Example 1 described in detail above, the following additional embodiments will be described. In Examples 2 to 4 (see the table below), parts similar to those in Example 1 will be omitted, and only the differences in some components will be described.
[0079] Table 2: Examples 2 to 4
[0080]
[0081]
[0082]
[0083] Test Examples
[0084] The room-temperature curable heat-resistant silicone coating of the present invention significantly realizes and improves the heat-resistant characteristics, as well as the heat and breakdown resistance characteristics. The coating of the present invention is particularly suitable for equipment or components operating under high-temperature and high-heat working conditions. The main test characteristics are shown in the following table (in the test examples, for the convenience of characterization, preparation and comparison, a coating thickness of 5 mm is uniformly used and coated on a stainless steel plate for testing):
[0085] Table 3: Heat insulation and heat resistance test of the room-temperature curable silicon-based nano-coating of the present invention
[0086]
[0087] Application Example 1:
[0088] A typical example of the application of the room-temperature curable environmentally friendly silicon-based nano-coating of the present invention includes a microfluidic chip. A schematic diagram of a typical microfluidic chip can be as Figure 1 shown. InFigure 1 In this case, the side walls of the pipes through which the fluid (including the aqueous phase and the oil phase) flows can be coated with the silicon-based nano-coating described in the embodiments of the present invention. The diameter of the side walls of the applicable pipes can range from several hundred micrometers to several millimeters (such as a pipe diameter of 800 μm to 10 mm). According to the processes and methods described below in the present invention, the hydrophilic-hydrophobic conversion of the inner or outer surface of the coated pipe can be achieved. Thus, the functions of guiding, separating, and mixing liquids can be realized in different regions. For example, in the regions where droplet coalescence is required, the coating remains hydrophobic to prevent liquid contact, while in the channels where liquid flow is required, the coating exhibits hydrophilicity to promote flow. Since the coating of the present invention has improved heat resistance and breakdown resistance, the microfluidic chip coated with the coating of the present invention can be applied to the fields of chemical and physical analysis under harsh and relatively high working conditions. For example, pressure detection equipment at high temperatures, biomedical and chemical analysis at high temperatures, etc.
[0089] It should be noted that the coating components in the embodiments of the present invention do not use highly toxic metal elements that damage the environment (such as Cr, Cd, Pb, etc.), nor do they basically use organic chemicals that volatilize toxic gases at high temperatures. Therefore, it can belong to an environmentally friendly paint or coating and is applicable to most application fields that require high temperature resistance or harsh working conditions.
[0090] In order to more clearly describe the application process in the coating of the present invention and the conversion process between hydrophilicity and hydrophobicity, the inventors represent the hydrophilic-hydrophobic conversion process of the coating in the embodiments of the present invention with Figure 2 a schematic diagram. In Figure 2 it is schematically described that the coating 104 of the embodiment of the present invention (or the comparative example described below) is applied to the substrate 103 (the substrate can be selected as a metal substrate, such as a stainless steel substrate). Electrode plates 102 are attached to both sides of the substrate 103 to which the coating 104 is applied; a heating sheet 105 is attached to one side of the electrode plate 102; and a DC power supply 101 is externally connected to the entire device.
[0091] In the actual operation process, the conversion between hydrophilicity and hydrophobicity can be achieved through the following technological process.
[0092] Hydrophilic conversion: Turn on the power supply, inject charges into the applied coating through a DC power supply (the DC voltage is set to 360 V) for a power-on time of 30 minutes to 10 hours; as the charging time increases, water droplets gradually cannot slide off the coating, achieving a super-hydrophilic state; during this period, the heater can also be used to moderately heat at a low temperature (for example, the heating temperature is controlled at 50 - 60 °C).
[0093] Hydrophobic conversion: When a hydrophobic surface is required, turn off the power supply and use a heating device to heat the coating and the substrate at a relatively high temperature (the heating temperature is controlled at, for example, 150°C to 160°C) to remove the charges in the coating. The heating time is 2 hours to 8 hours. After most of the net charges and polarities are removed, deionized water droplets can gradually slide off the surface of the coating and the substrate, becoming superhydrophobic.
[0094] In short, the coating of the present invention applies charges to the particles of the coating (especially the silica microparticles with different particle size ratios in the coating), making the coating have stronger polarity, enabling the hydrophilic transformation of water droplets. And by heating at a high temperature to remove most of the charges in the coating, the hydrophobic transformation is achieved.
[0095] Taking Example 1 as an example, the inventors tested the hydrophilic and hydrophobic properties of the coating of the present invention through the above method and device. The results are shown in Figure 3 and Figure 4 .
[0096] Figure 3 Schematically describes the gradual change of the contact angle between the coating of Example 1 of the present invention and water droplets during the hydrophilic conversion test. Initially, the surface of the coating of Example 1 shows a certain degree of hydrophobicity (about 105°). When the above-mentioned electrification process lasts for 2 hours, the contact angle (CA) changes to about 75°. After electrifying for 4 hours, the contact angle becomes about 14°. During the test, the temperature of the substrate and the coating is controlled at about 40°C by the heating device.
[0097] It is worth mentioning that the inventors found that when the contact angle becomes about 14 - 15°, increasing the electrification time (for example, up to 8 hours of electrification or longer), the contact angle will no longer decrease, which also exactly meets the expectations and designs of the inventors. In fact, in application examples (such as fluid control devices), it is not desired that the channels or coatings become completely hydrophilic or hydrophobic, because for example, a completely hydrophilic state will cause an undesired increase in the flow resistance of water droplets in the flow channel, while a completely hydrophobic state will cause the fluid flow rate to be too fast, resulting in stall and out-of-control.
[0098] Figure 4 Describes the hydrophobic conversion process. Under the condition of turning off the charge delivery, use a heater to heat the substrate and the coating at 150°C. When heating for 3 hours (after heating, stop and place it at room temperature for measurement, the same below), the contact angle reaches 152°. After heating for 6 hours, the contact angle reaches about 165°; on this basis, even if the heating time is further extended, the contact angle between the coating and the water droplets will no longer change significantly.
[0099] Similarly, as described above, the inventors actually need the hydrophobic angle of the coating not to reach complete hydrophobicity (close to 180°), preferably less than 170°, to achieve a better regulation state at the application end.
[0100] In the embodiments of the present invention, the contact angle between the coating and the water droplet can vary within a range of approximately 10° to 170°, and preferably, it is controlled to vary between approximately 15° and 165°.
[0101] Application Example 2
[0102] The coating of the present invention can also be applied to the top of new energy vehicles. In the field of the automotive industry in recent years, a large number of new energy vehicles tend to use large-area domes (such as glass, metal, or other materials) in the manufacturing process; under hot weather conditions, the automotive domes will be exposed to long-term sunlight, resulting in a decline in the user experience. However, the coating of the embodiments of the present invention can be applied to the top of new energy vehicles. On the one hand, the coating can withstand high-temperature exposure without cracking or peeling, and at the same time, the good temperature isolation effect also improves the riding experience of users in the car. Of course, when hydrophilic and hydrophobic conversion of the roof coating is required, the temperature change and the degree of voltage application involved should comply with the safety use standards of passenger cars. Appropriate hydrophilic and hydrophobic changes can also give the roof a good self-cleaning effect. Correspondingly, it can also be used on the surface of intelligent buildings that have emerged in recent years.
[0103] Application Example 3
[0104] The coating of the present invention can also be applied to other fields. For example, it can be applied to the outer surface of high-end buildings, as well as the surfaces of roads and concrete that require special properties. It can also play a role in increasing the temperature resistance performance and maintaining an appropriately controllable surface wetting performance.
[0105] Comparative Example
[0106] In this part, the comparative experiments corresponding to the examples will be described. For the convenience of description, the following content will ignore the parts that are the same as the examples, and focus on the components and / or process parameters that are different from the examples.
[0107] Comparative Example 1
[0108] In Comparative Example 1, the coating components and preparation process are basically the same as those in Example 1. The difference is that in Comparative Example 1, based on 100 wt% of the hydrophilic-hydrophobic regulation matrix, the three different particle sizes of silica particles described in Example 1 are not used; on the contrary, in Comparative Example 1, based on 100 wt% of the hydrophilic-hydrophobic regulation matrix, a single ultrafine silica particle with an average particle size (D50) of 20 nm is used.
[0109] Comparative Example 2
[0110] In Comparative Example 2, the coating components and preparation process were basically the same as those in Example 1. The difference was that in Comparative Example 2, based on 100 wt% of the hydrophilic-hydrophobic regulation matrix, the three different-sized silica particles described in Example 1 were not used; instead, in Comparative Example 1, based on 100 wt% of the hydrophilic-hydrophobic regulation matrix, 60 wt% of silica particles with an average particle size (D50) of 18 to 25 nm and 40 wt% of silica particles with an average particle size (D50) of 20 to 30 μm were used.
[0111] Comparative Example 3
[0112] In Comparative Example 3, the coating components and preparation process were basically the same as those in Example 1. The difference was that in Comparative Example 3, 50 parts by weight of the hydrophilic-hydrophobic regulation matrix were used relative to 200 parts by weight of the silicone oil base composition.
[0113] Comparative Example 4
[0114] In Comparative Example 4, the coating components and preparation process were basically the same as those in Example 1. The difference was that in Comparative Example 4, 20 parts by weight of aniline formaldehyde resin were not used. Instead, 20 parts by weight of polytetrafluoroethylene (PTFE) resin powder were used.
[0115] Test results of the comparative examples
[0116] For the above comparative examples, the same test items as in the examples were carried out. The test results are shown in the following table.
[0117] Table 4: Test results of the comparative experiments
[0118]
[0119] Generally speaking, the present invention relates to and realizes a room-temperature curable high-insulation heat-resistant and heat-proof coating, coating layer and its application. By adding powder fillers such as aniline formaldehyde resin and other organic components that have an electrostatic attraction to the benzene ring (tending to be negatively charged) of phenyl silicone rubber (the benzene ring amino group tends to be positively charged), the heat resistance of the coating layer is improved. At the same time, due to the opposite charge properties of the benzene ring on the silicone rubber and the benzene-amino group of the organic component, effective stacking can occur between the two, reducing the generation of defect structures. At the same time, materials with positive and negative polarities are combined with inorganic silica particles with a specific particle size distribution and possibly having pores when applying charge to control the polarity, which can control the overall charge distribution and content of the coating layer. Partial cancellation rather than complete cancellation can be achieved between the substrate and the applied charge, so that the contact wetting angle can be controlled to vary, for example, between about 15° and 165°, and will not reach an extremely hydrophilic (close to 0 degrees) or extremely hydrophobic (close to 180°) state due to excessive charge application or heating exceeding the threshold. This is preferred in many application scenarios in the field of infiltration control, and the breakdown field strength of the entire coating layer is as high as more than 23 kV / mm. The state of incomplete infiltration or incomplete hydrophobicity is beneficial for users to apply and control the corresponding surface.
[0120] Non-limitingly, for example, in Comparative Example 1, when all fine silica particles are used, the adjustable angle in the water contact angle regulation test becomes smaller. This may be because the charges accumulated in a large number of fine silica particles are less likely to be discharged by the heating process compared to large silica particles. Therefore, more residual static charges inevitably accumulate inside the coating, resulting in the inability to achieve a non-polar superhydrophobic property. On the other hand, during the charging process, the charge characteristics of silica particles with small cavities may also be affected. Therefore, the superhydrophilic property during the polarization process is also affected. The inventors also found that when only fine silica fillers are used, the thermal conductivity also increases (the heat insulation effect deteriorates slightly). It can be seen that a certain proportion of relatively large silica fillers can not only maintain effective charge charging and discharging efficiency but also effectively support the thermal conductivity of the coating. At the same time, the corresponding heat resistance also slightly decreases in Comparative Example 1 (i.e., the temperature on the side of the coating away from the heat source increases during the heat resistance test). When a combination of single fine particles and large-sized silica particles is used in the coating (such as in Comparative Example 2), although the specific heat capacity and heat resistance are guaranteed to a certain extent, the inventors found that the charge breakdown resistance of the coating significantly decreases. This may be because the large silica (hollow) particles result in poor coating uniformity, causing the voltage to break through from the thinner (or uneven) part of the coating during the voltage breakdown experiment, resulting in a decrease in compressive capacity. Similarly, the inventors found that when the proportion of the matrix (similar to the coating aggregate) is adjusted too large (Comparative Example 3), for example, when the hydrophilic-hydrophobic regulation matrix exceeds 25 wt% or 30 wt% of the silicone oil base composition, the adhesion and breakdown resistance of the coating decrease. This may also be due to the excessive amount of silica particles leading to a decrease in coating uniformity. At the same time, in practical applications, too many matrix components will cause uneven coating thickness in, for example, fluid control pipelines, affecting the smoothness of the pipeline's control of fluids. In a large-area coating area such as the top of a new energy vehicle, it will cause uneven top coating or local over-protrusion, thus affecting the aesthetics and service life of the large-area coating.
[0121] In a preferred embodiment of the present invention, the mass ratio of the silicone oil base composition to the hydrophilic-hydrophobic regulation matrix is preferably between 10:(1 - 2), which is beneficial to obtaining balanced and improved coating properties.
[0122] When the inventor uses non-polar polytetrafluoroethylene filler to replace aniline formaldehyde (tending to carry a + charge) resin with a benzene ring - amino structure (Comparative Example 4), the components of phenyl vinyl silicone oil and phenyl hydrogen-containing silicone oil that tend to carry a negative charge are lost in the matrix. Due to the charge in the matrix, the polarity of the coating cannot be largely eliminated, resulting in the contact angle in hydrophobic regulation not exceeding 135°, and in the hydrophilic test, the phenomenon of an extremely hydrophilic surface easily occurs (which is disadvantageous in the field of fluid control), which increases the difficulty of control in terms of the regulation of surface wettability.
[0123] According to the embodiments and technical content described in the specification of the present invention, the present invention can at least provide the following technical solutions: Although the present disclosure includes specific embodiments, it is obvious to those skilled in the art that various substitutions or changes in form and detail can be made to these embodiments without departing from the inventive points and scope of the claims and their equivalent technical solutions. The embodiments described herein should be considered only in an illustrative sense and not for the purpose of limitation. The description of the features and aspects in each embodiment is considered applicable to the similar features and aspects in other embodiments. Therefore, the scope of the present disclosure should not be limited by the specific description, but by the claims of the technical solutions, and all changes within the scope of the claims and their equivalents are construed as being included in the technical solutions of the present disclosure.
Claims
1. A room-temperature curable silicone-based nano-coating, characterized in that, The silicon-based nano-coating contains raw materials of the following components by weight parts: Silicone oil base composition: 150 to 200 weight parts; Hydrophilic-hydrophobic regulation matrix: 15 to 35 weight parts; Matrix reinforcing fiber: 5 to 30 weight parts; Aniline formaldehyde resin: 10 to 30 weight parts; Diluent: 10 to 30 weight parts; and wherein the silicone oil base composition includes an epoxy group-terminated silicone oil with a weight-average molecular weight of 10,000 to 12,000, a bifunctional phenyl vinyl silicone oil with a weight-average molecular weight of 600 to 800, a bifunctional phenyl hydrogen-containing silicone oil with a weight-average molecular weight of 600 to 900, and an adhesion enhancement component; and wherein the hydrophilic-hydrophobic regulation matrix includes silica particles with two or more different particle size distributions.
2. The room-temperature curable silicon-based nano-coating according to claim 1, wherein The hydrophilic-hydrophobic regulation matrix includes silica particles with three different particle size distributions, and wherein the first silica particle is nano-silica with an average particle size (D50) of 8 to 15 nm, which accounts for 10 wt% to 20 wt% of the total mass of the silica particles; The second silica particle is nano-silica with an average particle size (D50) of 50 to 75 nm, which accounts for 30 wt% to 45 wt% of the total mass of the silica particles; The third silica particle is silica particle with an average particle size (D50) of 1 to 3 microns, which accounts for 40 wt% to 50 wt% of the total mass of the silica particles; and The mass ratio of the silicone oil base composition to the hydrophilic-hydrophobic regulation matrix is between 10:(1 - 2).
3. The room temperature curing type silicon-based nano-coating according to claim 1 or 2, characterized in that, Calculated based on 100 wt% of the total weight of the silicone oil base composition, the silicone oil base composition includes: 25 wt% to 30 wt% of an epoxy group-terminated silicone oil with a weight-average molecular weight of 10,000 to 12,000; 55 wt% to 60 wt% of a bifunctional phenyl vinyl silicone oil with a weight-average molecular weight of 600 to 800; 5 wt% to 10 wt% of a bifunctional phenyl hydrogen-containing silicone oil with a weight-average molecular weight of 600 - 900; 0.5 wt% to 1 wt% of an adhesion enhancement component; 0.1 wt% to 1 wt% of a control agent; and Anhydrous ethanol as a solvent.
4. The room-temperature curable silicone-based nano-coating according to any one of claims 1 to 4, characterized in that, The room-temperature curing silicon-based nano-coating also satisfies one or more of the following conditions: The matrix reinforcing fiber is quartz fiber with an average length of 20 to 40 microns and an aspect ratio greater than 10:1; The diluent is ethyl acetate; The room-temperature curing silicon-based nano-coating contains tetrabutyl titanate as an auxiliary catalyst; and The hydrophilic-hydrophobic regulation matrix is prepared by mixing and stirring the silica particles with tetraethyl orthosilicate and heptadecafluorodecyltrimethoxysilane.
5. The room-temperature curable silicon-based nano-coating according to any one of claims 1 to 4, characterized in that, The room-temperature curing silicon-based nano-coating is prepared by a method including the following steps: Step 1): Prepare each raw material component of the silicone oil base composition, and stir each component evenly in a blender to obtain the silicone oil base composition; Step 2): Prepare 5 to 10 parts by weight of deionized water, put the measured silica particles of the hydrophilic-hydrophobic regulation matrix into the mixed solution and stir; subsequently, add tetraethyl orthosilicate accounting for 5 wt% to 10 wt% of the total solid content in the above hydrophilic-hydrophobic regulation matrix and 1 wt% to 5 wt% of 1,1,2,2,3,3,4,4,5,5,6,6,7,7,7-heptadecafluorodecyltrimethoxysilane, and stir thoroughly until there is no stratification in the mixed system; Obtain the hydrophilic-hydrophobic regulation matrix; Step 3): Mix the above hydrophilic-hydrophobic regulation matrix with the silicone oil base composition, add the corresponding parts by weight of reinforcing fibers, and stir to obtain a first intermediate; Step 4): Add aniline formaldehyde resin with a corresponding ratio to the first intermediate, and mix to obtain a second intermediate; Step 5): Mix the second intermediate with 3 - 5 parts by weight of auxiliary catalyst, and then add the corresponding parts by weight of diluent, and stir and mix to obtain a room-temperature curable silicone-based nano-coating.
6. A preparation method of a room-temperature curable environmentally friendly silicone-based nano-coating, characterized in that, Apply the room-temperature curable silicone-based nano-coating according to any one of claims 1 to 5 to the surface of a device or a substrate, and cure at room temperature for 96 to 120 hours to obtain the silicone-based nano-coating.
7. According to the preparation method of the room-temperature curable environmentally friendly silicone-based nano-coating described in claim 6, characterized in that, The thickness of the silicone-based nano-coating is between 500 microns and 5 millimeters.
8. Application of a room-temperature curing environmentally friendly silicon-based nano-coating, characterized in that, Apply the coating prepared by the preparation method of the room-temperature curable environmentally friendly silicone-based nano-coating according to any one of claims 6 or 7 to the surface of the pipeline of a microfluidic device, the outer surface of a building, the road surface or the outer surface of a new energy vehicle.
9. The application of the room-temperature curing environmentally friendly silicon-based nano-coating according to claim 8, characterized in that, After the coating is applied to the corresponding surface, the wetting angle between the coating surface and the water droplet changes between 10° and 170°.
Citation Information
Patent Citations
Organosilicon superhydrophobic nano-composite coating, and preparation method and use thereof
CN102963087A
Patterned polymer and preparation method thereof
CN107880302A
Composite nano-coating material with hydrophobic and anticorrosive performances, and preparation method and application thereof
CN110205023A
Material surface hydrophilic and hydrophobic liquid patterning treatment method and application
CN113814147A
Modified epoxy resin-based wear-resistant super-hydrophobic coating and preparation method thereof
CN117511328A